Nitrous Oxide Fluxes in Permafrost Peatlands Remain Negligible After Wildfire and Thermokarst Disturbance. Issue 4 (19th April 2023) - Schulze, Christopher; Sonnentag, Oliver; Voigt, Carolina; Thompson, Lauren; van Delden, Lona; Heffernan, Liam; Hernandez‐Ramirez, Guillermo; Kuhn, McKenzie; Lin, Sisi; Olefeldt, David
Abstract: The greenhouse gas (GHG) balance of boreal peatlands in permafrost regions will be affected by climate change through disturbances such as permafrost thaw and wildfire. Although the future GHG balance of boreal peatlands including ponds is dominated by the exchange of both carbon dioxide (CO2 ) and methane (CH4 ), disturbance impacts on fluxes of the potent GHG nitrous oxide (N2 O) could contribute to shifts in the net radiative balance. Here, we measured monthly (April to October) fluxes of N2 O, CH4, and CO2 from three sites located across the sporadic and discontinuous permafrost zones of western Canada. Undisturbed permafrost peat plateaus acted as N2 O sinks (−0.025 mg N2 O m −2 d −1 ), but N2 O uptake was lower from burned plateaus (−0.003 mg N2 O m −2 d −1 ) and higher following permafrost thaw in the thermokarst bogs (−0.054 mg N2 O m −2 d −1 ). The thermokarst bogs had below‐ambient N2 O soil gas concentrations, suggesting that denitrification consumed atmospheric N2 O during reduction to dinitrogen. Atmospheric uptake of N2 O in peat plateaus and thermokarst bogs increased with soil temperature and soil moisture, suggesting sensitivity of N2 O consumption to further climate change. Four of five peatland ponds acted as N2 O sinks (−0.018 mg N2 O m −2 d −1 ), with no influence of thermokarst expansion. One pond with high nitrate concentrations had high N2 O emissions (0.30 mg N2 O m −2 d −1 ). Overall, our study suggests that the future net radiative balance of boreal peatlands will be dominated by impacts of wildfire and permafrost thaw on CH4 and CO2 fluxes, while the influence from N2 O is minor. Plain Language Summary: The peatlands in the boreal biome of northwestern Canada have been a sink of the potent greenhouse gases (GHG) carbon dioxide (CO2 ) and nitrous oxide (N2 O), and a source of methane (CH4 ) for many millennia. Now, climate change is transforming these boreal peat landscapes as more severe and frequent wildfires burn the forests and ground ice‐rich permafrost thaws. Wildfires and permafrost thaw alter soil biogeochemical conditions such as soil temperature, soil moisture, and water table depth. The changing conditions have immediate effects on GHG production, transport, and consumption in the soil, which are reasonably well understood for CO2 and CH4 but not for N2 O. By measuring soil GHG concentrations at different depths and GHG exchange between soil and atmosphere with static chambers, we showed that N2 O exchange from different peat surfaces responded differently depending on the two disturbance types. While burned peatland areas were close to neutral regarding N2 O, the wet, thaw‐affected areas showed increased N2 O uptake driven by high soil moisture contents, soil temperatures, and below‐atmospheric N2 O soil gas concentrations. However, this minor N2 O uptake can only offset less than 1% of the global warming potential of CH4 emissions from the thawing peatlands studied here. Key Points: Permafrost peatlands acted as sinks of nitrous oxide; thermokarst and wildfire caused increased and reduced uptake rates, respectively Uptake of nitrous oxide in peat plateaus and thermokarst bogs increased with soil temperature, suggesting sensitivity to climate warming Impacts of thermokarst and wildfire on nitrous oxide fluxes were minor compared to methane when expressed in carbon dioxide equivalents